Inclusive-Exclusive Distinction in the Kirati Languages: Evidence from Dungmali, Khaling, Koyee, and Wambule - Rai, Tara Mani (Perspectives on Higher Education, 2024)
This study conducts a comparative analysis of the inclusive and exclusive distinctions among the Kirati languages, specifically Dungmali, Khaling, Koyee, and Wambule. Data were collected through direct elicitation from native speakers, revealing the presence of inclusive and exclusive distinctions in both non past intransitive and transitive verb paradigms. Among the languages examined, Wambule, Koyee, and Khaling exhibit a closer affinity in terms of the first person dual inclusive and exclusive distinctions. For first person plural inclusive and exclusive, Koyee, and Khaling share common markers, suggesting a linguistic proximity between them. In contrast, Wambule and Dungmali display similarities, particularly in their utilization of the nasal marker <-n> for first person plural inclusive, although Dungmali employs nasals more extensively than Wambule, particularly for first person plural exclusive marking. In the non past transitive paradigm, Khaling, Koyee, and Wambule demonstrate greater similarity, employing the first person dual-inclusive marker <tsi> and exclusive marker <-tsu> in pronoun form, albeit with nuanced variations in predicates. For first person plural inclusive and exclusive, Khaling and Koyee utilize the marker <-ki> and its reverse form <ik>, respectively. In contrast, Dungmali stands out by incorporating nasals alongside the marker <n~ŋa> to denote first person plural inclusive and exclusive, distinguishing it from the other languages under examination.